Narasi Term Zholim Dalam Tafsir al-Wasith Karya Wahbah al-Zuhaili - Desri Ari Enghariano (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2021)
Islam is a mercy for the universe. But in reality, many people don’t want to make Islam the compas of life. This makes them be oppressor. The scholars, especially Wahbah al-Zuhaili have warned in one of his book, namely Tafsir al-Wasith not do oppression. Therefore, this research aims to describe the narration of the term oppression in Tafsir al-Wasith; in the form of the definition of oppression, the history of oppression, various kinds of oppression, triggering factor for doing of oppression, and punishment for oppressor. The method used in this research is thematic method. The results of this research is to explain that the meaning of oppression is attitudes and actions that goes beyond  the corridor. Oppression acts in history began with the prophet Adam. There are three kinds of oppression; namaely oppression to Allah, oppression to one’s own person, and oppression to other people. There are three triggering factors for doing oppression; namely fear of the creatures more than fear of the Creator, weak faith in the Day of Judgment, and raises doubt about the justice of Allah. Oppressor will be punished for his oppression; both the punishment of this world and the punishment of the hereafter.